2011
DOI: 10.1007/s11248-011-9554-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of cloned transgenic cow expressing omega-3 fatty acids

Abstract: n-3 Polyunsaturated fatty acids (n-3 PUFA) are important for human health. Alternative resources of n-3 PUAFs created by transgenic domestic animals would be an economic approach. In this study, we generated a mfat-1 transgenic cattle expressed a Caenorhabditis elegans gene, mfat-1, encoding an n-3 fatty acid desaturase. Fatty acids analysis of tissue and milk showed that all of the examined n-3 PUAFs were greatly increased and simultaneously the n-6 PUAFs decreased in the transgenic cow. A significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 25 publications
1
60
1
Order By: Relevance
“…Moreover, the DHA content in white adipose tissue increased by 19% (Ji et al, 2009). Wu et al (2012) generated an mFat-1 transgenic calf, and found that the n-3 PUFA content increased in all samples, whilst that of n-6 PUFAs simultaneously decreased. Interestingly, the ratios of n-6/n-3 PUFAs in tissues and milk significantly decreased (Wu et al, 2012).…”
Section: High Performance Gas Chromatography Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the DHA content in white adipose tissue increased by 19% (Ji et al, 2009). Wu et al (2012) generated an mFat-1 transgenic calf, and found that the n-3 PUFA content increased in all samples, whilst that of n-6 PUFAs simultaneously decreased. Interestingly, the ratios of n-6/n-3 PUFAs in tissues and milk significantly decreased (Wu et al, 2012).…”
Section: High Performance Gas Chromatography Analysismentioning
confidence: 96%
“…The hFat-1-neo+, hFat-1-neo-, and PFF cells were cultured with 60 μM arachidonic acid for 48 h. Cells were then trypsinized for 3 min using 0.05% trypsin, and lipids were extracted as previously reported (Wu et al, 2012). Briefly, the cells were homogenized in a mixture of methanol, chloroform, and water.…”
Section: High-performance Gas Chromatography Analysis Of Fatty Acids mentioning
confidence: 99%
“…Simultaneously, fat-1 gene expression substantially reduced the n-6/n-3 PUFA ratio in tissue and milk. As the authors concluded, their results demonstrated that the transgenic fat-1 cow was characterised by normal reproduction and gave milk with improved fatty-acid composition, which might become an economically efficient approach to meet the increasing human demand for n-3 PUFAs (Wu et al, 2012).…”
Section: Modifications Of the Composition Of Milk Lipidsmentioning
confidence: 97%
“…A cloned transgenic cow expressing a fat-1 transgene from C. elegans and encoding an n-3 fatty-acid desaturase was generated by Wu et al (2012). The transgenic cow was healthy, and after artificial insemination became pregnant and delivered a healthy calf naturally.…”
Section: Modifications Of the Composition Of Milk Lipidsmentioning
confidence: 99%
See 1 more Smart Citation